The Empirical Analysis of Family Maintenance Dynamics in Fiqh Munākaḥāt: A Socio-Legal Study of Muslim Families in Pekanbaru - Hikmatullah, Hikmatullah; Bon, Abdul Talib (Islamica: Jurnal Studi Keislaman, 2026)
This study aims to analyze the dynamics of livelihood practices in Muslim families in Pekanbaru City and explain the relationship between the norms of fiqh munakahat and social reality through a socio legal approach. The study used a qualitative method with data collection techniques including in depth interviews, observation, and documentation. The results show that livelihood practices in Muslim families are dynamic and divided into three main patterns: normative, collaborative, and collective. Economic factors are the main determinant driving changes in livelihood practices, especially in the context of the pressures of life’s needs in urban areas. Meanwhile, educational and social factors play a role in shaping perspectives and relationship patterns within the family. These findings indicate that livelihood practices are the result of the interaction between fiqh norms and social reality. Conceptually, this study confirms that fiqh munakahat has an adaptive capacity to respond to social change through the principles of justice, benefit, and propriety. Therefore, variations in maintenance practices cannot be understood as deviations, but rather as a contextualization of sharia values in contemporary Muslim family life. This research contributes to the development of Islamic family law studies that are more contextual, empirical, and responsive to social dynamics.